Identification of rhizobacteria isolate from Bali Barat National Park, Indonesia and the potential as biological agents against soybean seed-borne pathogen - KHAMDAN KHALIMI; IDA BAGUS GEDE PRANATAYANA; KETUT AYU YULIADHI; I WAYAN DIKSA GARGITA; I KADEK WISMA YUDHA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Khalimi K, Pranatayana IBG, Yuliadhi KA, Gargita IWD, Yudha IKW. 2025. Identification of rhizobacteria isolate from Bali Barat National Park, Indonesia and the potential as biological agents against soybean seed-borne pathogen. Biodiversitas 26: 1799-1806. The use of biological agents is a method of suppressing plant pathogenic fungi. Therefore, this study aimed to determine biochemical characteristics, identity, antifungal activity, and types of compounds produced by rhizobacteria isolates from Taman National Bali Barat (West Bali National Park/TNBB), Bali, Indonesia. Rhizobacteria was characterized using Microbact Biochemical Kits and molecular identification of rhizobacteria based on the 16S rRNA gene sequence analysis. Antifungal compounds were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). The results showed that rhizobacteria used gelatin and arabinose as carbon sources, producing indole, acetoin, urease, and tryptophan deaminase compounds. The identity of rhizobacteria isolate TNBB is Bacillus thuringiensis. Furthermore, rhizobacteria filtrate of TNBB isolate inhibited the growth of Alternaria alternata, Aspergillus flavus, Aspergillus parasiticus, Aspergillus ochraceus, Aspergillus niger, Aspergillus tubingensis, Aspergillus aculeatus, and Rhizopus oryzae fungi. The diameter of the inhibition zone formed was categorized as having very strong power. The filtrate of TNBB isolate rhizobacteria contained 16 antifungal compounds, namely 1,3,5-triazine-2,4,6-triamine, 2(1H)-pyridinone 6-hydroxy-, tridecanoic acid, N-acetyl-d-glucosamine, hexadecanoic acid, butanoic acid, pentyl ester, pentanoic acid butyl ester, pentanoic acid pentyl ester, linoleic acid, 1-naphthalene-sulfonic acid, 2-naphthalene-sulfonic acid, stearic acid, cyclotrisiloxane hexamethyl-, cyclotrisiloxane hexamethyl, 1,2-benzenedicarboxylic acid, diisooctyl ester, and benzo[h]quinoline, 2,4-dimethyl-. The results of this study provided information that TNBB isolate rhizobacteria are suitable for use as biological agents.